Specific Language Impairment: A neuropsychological characterization - Coelho, Sandra (2013)
This study’s objective was to characterize the neuropsychological functioning of children with Specific Language Impairment (SLI), in the areas of visual and verbal memory, attention/executive functions, and visual-perceptual functions. The sample consisted of 28 children with SLI and 28 children without SLI. Both groups were comparable in terms of age, gender, school grade and socioeconomic level. The assessment instruments used are part of Coimbra's Neuropsychological Assessment Battery and data were analyzed through parametric and nonparametric statistical tests. In general, the results differentiate the performances of children with SLI from those observed in children without SLI. In comparison to the control group, the group of children with SLI obtained poorer results in visual memory and verbal memory, selective and sustained attention, executive functions, semantic verbal fluency, visual-perceptual functions and processing speed.